PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN PADA VILLA THE LEAF JIMBARAN - Ni Luh Putu Ayu Anggi Pratiwi; I Putu Bagus Suthanaya (Journal Research of Management, 2022)
This research aims to analyze the effects of leadership and communication on employees job satisfaction. The population in this study at Villa The Leaf located in Jimbaran. The method of determining sampling uses a saturated sample. In this study the number of samples was 56 employess.And secondary datain the form of library research in the form of journals and book as well as accessing websites and sites related to research. Data analysis techniques used in research use linear reggresion analysis used todetermine theeffect of independent variables on thedependent variable. The results of this study indicate that leadership has a significant positive effect on employees job satisfaction this results indicate that leadership has score of t count is 3,004 more bigger than score t table in the amount of 1,669 with significant value is 0,004 more smaller than 0,05. And communication has asignificant positive effect on employees job satisfaction, this study indicate that communication has score of t count is 2,168 more bigger than t table in the amount of 1,669 with significant value is 0,035 more smaller than 0,05.